2018
DOI: 10.1002/cjce.23309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonic cavitation on neutralization process of low molecular weight polyethylene glycol

Abstract: In recent decades, ultrasound has been broadly employed in different applications, particularly in the chemical industry. Ultrasound enhances chemical reactions in a solution via generation of cavitation microbubbles. It improves mass transfer rate and kinetic rate of targeted systems under various process conditions. In polyethylene glycol (PEG) production, the neutralization reaction is generally carried out by employing a mechanical stirring operation. However, this process produces a soluble salt containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Further, when a chemical reaction begins, the acoustic power is optimal for a maximal reaction rate. High US power generates more bubbles, obstructing the flow of acoustic energy [ 29 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, when a chemical reaction begins, the acoustic power is optimal for a maximal reaction rate. High US power generates more bubbles, obstructing the flow of acoustic energy [ 29 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carbon capture and storage (CCS) is considered a promising approach to decrease the climate change progress and to accomplish the Paris Agreement expectations. 1 It is estimated that CCS contributes to a 14% decrease in the world CO 2 emissions under the 2 °C scenario (i.e., to limit the global temperature increase below 2 °C) and a further 32% under the beyond 2 °C scenario. 2 The concentration of CO 2 in the atmosphere is constantly increasing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Therefore, it is expected to be applicable to the fabrication of other nanoparticles. Azarpour et al [ 36 ] studied the effect of ultrasonic cavitation on the neutralization process of polyethylene glycol and compared it with the mechanical stirring method. It is confirmed that the addition of ultrasonic power reduced the conductivity and soluble salt content in the solution.…”
Section: Introductionmentioning
confidence: 99%